Serotonergic perturbations in dystonia disorders—a systematic review. (June 2016) - Smit, M.; Bartels, A.L.; van Faassen, M.; Kuiper, A.; Niezen- Koning, K.E.; Kema, I.P.; Dierckx, R.A.; de Koning, T.J.; Tijssen, M.A.
Highlights: We examined the role of serotonin in inherited, acquired and idiopathic dystonia. Most studies point towards a hypofunction of the serotonergic system in dystonia. Serotonergic/dopaminergic imbalances may be an important modulator of dystonia. High prevalences of psychiatric co-morbidity may suggest serotonergic dysfunction. Influencing serotonin may form a new potential target for therapeutical interventions. Abstract: Dystonia is a hyperkinetic movement disorder characterized by sustained or intermittent muscle contractions. Emerging data describe high prevalences of non-motor symptoms, including psychiatric co-morbidity, as part of the phenotype of dystonia. Basal ganglia serotonin and serotonin-dopamine interactions gain attention, as imbalances are known to be involved in extrapyramidal movement and psychiatric disorders. We systematically reviewed the literature for human and animal studies relating to serotonin and its role in dystonia. An association between dystonia and the serotonergic system was reported with decreased levels of 5-hydroxyindolacetic acid, the main metabolite of serotonin. A relation between dystonia and drugs affecting the serotonergic system was described in 89 cases in 49 papers. Psychiatric co-morbidity was frequently described, but likely underestimated as it was not systematically examined. Currently, there are no good (pharmaco)therapeutic options for most forms of dystonia or associated non-motor symptoms. Further research using selective serotonergic drugs in appropriate models of dystonia is required to establish the role of the serotonergic system in dystonia and to guide us to new therapeutic strategies.